2019
DOI: 10.14639/0392-100x-2155
|View full text |Cite
|
Sign up to set email alerts
|

Management of idiopathic epistaxis in adults: what’s new?

Abstract: SUMMARYEpistaxis is one of the most common complaints presenting to emergency departments. The aim of this study is to systematically review and critically evaluate the evidence relating to treatment of idiopathic epistaxis for guiding best practice. A comprehensive review of the English language literature was performed using PubMed, Embase, Cochrane Library and Central electronic databases. The inclusion criteria were: retrospective or prospective or randomised controlled clinical trials which included outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“… 10 Cauterization as a treatment option is more viable if the source of bleeding can be identified, and provides economic advantages compared to the cost of nasal packing. 2 , 10 , 11 Cauterization should be used if the location of the bleed can be identified in cases of anterior epistaxis. 12 If the bleeding site is not identified or cauterization is not available, nasal packing is required, which leads to them being closely related in the clinical care pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 Cauterization as a treatment option is more viable if the source of bleeding can be identified, and provides economic advantages compared to the cost of nasal packing. 2 , 10 , 11 Cauterization should be used if the location of the bleed can be identified in cases of anterior epistaxis. 12 If the bleeding site is not identified or cauterization is not available, nasal packing is required, which leads to them being closely related in the clinical care pathway.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Absorbable packing can be used in both anterior and posterior epistaxis, though it is more typically involved in anterior epistaxis. 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This forms an eschar that obstructs and scleroses blood vessels [ 9 ]. Prior studies have shown that failure rates of silver nitrate can be quite high, ranging from 16% to 26% [ 10 , 11 ]. No serious adverse effects have been associated with nasal silver nitrate cautery, but pain is often reported [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some cases of recurrent epistaxis where the bleeding site is deep and difficult to manage (12,13) . In line with recent uprising in endoscopic nasality sinus surgery, endoscopic cauterization of the sphenopalatine artery is now used for posterior epistaxis (14) . Therefore, the current study aimed to evaluate the efficacy of this surgical procedure for a group of patients suffering from idiopathic refractory posterior epistaxis.…”
Section: Introductionmentioning
confidence: 99%